Analyzing the Impact of 3D Printing on the Development of Engineering Design Models Using CAD Software - Abdu Esslam Soliman Abduesslam Omar (African Journal of Advanced Pure and Applied Sciences, 2025)
The purpose of this study is to make a numerical a priori comparison concerning the FDM and the SLA-related errors concerning the creation of a standard geometric pattern with multiple features like small cylindrical lbosses, narrow walls, and angled surfaces, which are each special features concerning their sensitivity to detail replication. The authors’ overall approach consisted of designing within Autodesk Fusion 360 with exact nominal values, taking notes, and then exporting and rendering a high-quality STL file. The layering during printing involved Ultimaker Cura for FDM with a layer height setting of 0.20 mm with PLA material, while layer height setting values between 0.05 and 0.10 mm were applied while using Photon Workshop software concerning SLA printing;, post-curing subsequently ensued to make both FDM and SLA prints dimensionally stable. To measure the exact dimensions, a precision Digital Caliper with a precision value of ±0.01 mm was deployed to measure each dimension, taking three attempts per measurement to assess exact values concerning both absolute and relative error. The results revealed significantly higher error values concerning FDM printing: The 6 mm boss differed on average by 6.12 mm (+0.12 mm, +2.00%) to its exact nominal dimension, while the 0.6 mm wall varied to 0.66 mm (+10%) to its exact nominal dimension, and finally, the height value concerning the wedge surface varied to 17.90 mm (+1.70%) to its exact nominal dimension. On the other hand, SLA performed more uniformly and precisely, with respect to the same boss at 6.04 mm (+0.04 mm; +0.67%), wall 0.61 mm (+1.67%), and wedge 17.70 mm (+0.57%), with a total average deviation of +0.05 mm over +0.16 mm for FDM. Therefore, these experiments verify successfully both the superiority of SLA in terms of precision to represent geometrically minute features and that any kind of actual geometric compensation within FDM technology is possible only via deliberate geometric compensations on the CAD design model level. This paper thus confirms again the crucial integration required between actual dimensional metrology and designing on a CAD level to enhance, rather than impede, an understanding about dynamics of accuracy according to DfAM philosophy and concepts.